2023
DOI: 10.3390/healthcare11152210
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Autoantibodies on Non-Hodgkin Lymphoma

Sonia Guadalupe Barreno-Rocha,
Sandra Guzmán-Silahua,
Ernesto Germán Cardona-Muñoz
et al.

Abstract: (1) Background: Non-Hodgkin Lymphoma is a neoplasm that can significantly compromise the immune system, but timely assessment can change the patient outcome. In cancer, the activation of the immune system could lead to the secretion of autoantibodies. (2) Methods: A retrospective cohort study was performed from 2017 to 2019 in patients with Non-Hodgkin Lymphoma diagnosed with a biopsy. (3) Results: We included 39 patients who were newly diagnosed, untreated, and without any autoimmune disease previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(32 reference statements)
0
4
1
Order By: Relevance
“…Charlotte Mörth et al found a significantly increased prevalence of ANA in females, which is already established for AD in general [5]. Regarding the association of ANA with the type of lymphoma, the AABC subtype of DLBCL has a higher tendency for AD and obviously for ANA too [14,10,3]. Contrary to this, we noticed ANA positivity in only 33% (03/10) of DLBCL-non-GCB and 36% (13/36) of overall DLBCL, respectively.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Charlotte Mörth et al found a significantly increased prevalence of ANA in females, which is already established for AD in general [5]. Regarding the association of ANA with the type of lymphoma, the AABC subtype of DLBCL has a higher tendency for AD and obviously for ANA too [14,10,3]. Contrary to this, we noticed ANA positivity in only 33% (03/10) of DLBCL-non-GCB and 36% (13/36) of overall DLBCL, respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…AD as a risk factor for the development of lymphoma is relatively better established; yet, the prevalence of AD diseases in patients with lymphoma and their impact on the outcome of this malignancy is relatively less explored [1,5,6]. Prevalence of AD in DLBCL patients has ranged from 17.3% to 22.5% as compared to the general population (03-13.8%) [5,6,8] [9][10][11]. Most of the earlier reports have some limitations like the random time of recruitment (before/after therapy), retrospective data, and variable definition of AD (based only on clinical features without biological markers) [1,5,9,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hospital-based case-control study reported a higher prevalence of ANA as well as other autoimmune antibodies among lymphoma patients compared to healthy controls [29]. A retrospective cohort study found that 77% of non-Hodgkin lymphoma patients had autoantibodies at the time of diagnosis, with 44% of those testing positive for ANA [31]. Although we did not observe an increased risk of NHL overall with ANA in our study, we did observe a higher risk of NHL with the presence of at least one other autoimmune antibody.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell non-Hodgkin lymphoma (NHL) collectively represents the most common type of hematologic malignancy [ 1 ]. While advances in chemotherapy, monoclonal antibodies, and stem cell transplantation have improved survival rates, many NHL patients remain resistant to therapy or experience relapse.…”
Section: Introductionmentioning
confidence: 99%